2017
DOI: 10.3847/1538-4357/aa7a59
|View full text |Cite
|
Sign up to set email alerts
|

Microflare Heating of a Solar Active Region Observed with NuSTAR, Hinode/XRT, and SDO/AIA

Abstract: NuSTAR is a highly sensitive focusing hard X-ray (HXR) telescope and has observed several small microflares in its initial solar pointings. In this paper, we present the first joint observation of a microflare with NuSTAR and Hinode/ XRT on 2015 April 29 at ∼11:29 UT. This microflare shows the heating of material to several million Kelvin, observed in soft X-rays with Hinode/XRT, and was faintly visible in the extreme ultraviolet with SDO/AIA. For three of the four NuSTAR observations of this region (pre-flare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 45 publications
13
74
0
1
Order By: Relevance
“…In this paper, we presented the smallest microflare seen yet with NuSTAR , about an order of magnitude weaker than those previously observed with NuSTAR (Wright et al 2017;Glesener et al 2017) and well beyond the microflares observed with RHESSI (Hannah et al 2008a). This event is similar in thermal energy to quiet Sun flares seen with NuSTAR (Kuhar et al 2018), however the microflare presented in this paper demonstrates higher temperature emission and is from an active region.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In this paper, we presented the smallest microflare seen yet with NuSTAR , about an order of magnitude weaker than those previously observed with NuSTAR (Wright et al 2017;Glesener et al 2017) and well beyond the microflares observed with RHESSI (Hannah et al 2008a). This event is similar in thermal energy to quiet Sun flares seen with NuSTAR (Kuhar et al 2018), however the microflare presented in this paper demonstrates higher temperature emission and is from an active region.…”
Section: Discussionsupporting
confidence: 44%
“…It has targeted the Sun several times since the first pointing in late 2014 , and has observed active region microflares as well as quiet Sun brightenings. These microflares are about an order of magnitude weaker than RHESSI could observe, down to an estimated GOES level of ∼A0.1, and showed heating up to about 10MK, with thermal energies of 10 27 erg (Wright et al 2017;Glesener et al 2017). These events were also well observed at longer wavelengths, in softer X-rays with Hinode/XRT and the Solar Dynamics Observatory/Atmospheric Imaging Assembly (SDO/AIA ).…”
Section: Introductionmentioning
confidence: 77%
“…Other NuSTAR microflares are the subjects of recent or upcoming papers, including one by Wright et al (2017) that shows a detailed differential emission measure obtained via Hinode XRT coordination. We expect future NuSTAR events with higher livetime and correspondingly better statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the events that have been studied with RHESSI are much larger than those considered here, though. Recently, NuSTAR, the very sensitive astrophysics mission, has also been used to observe quiescent active regions, and on one occasion a microflare was observed, as described in Wright et al (2017). Although the NuSTAR resolution does not allow to resolve spectral lines, the (thermal) continuum measurements indicated very low temperatures (of the order of 3-5 MK) for the event of GOES class A0.1.…”
Section: A Short Overview Of Microflare Observationsmentioning
confidence: 99%